2012
DOI: 10.2478/v10266-012-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Models and Algorithms for Production Planning and Scheduling in Foundries - Current State and Development Perspectives

Abstract: Mathematical programming, constraint programming and computational intelligence techniques, presented in the literature in the field of operations research and production management, are generally inadequate for planning real-life production process. These methods are in fact dedicated to solving the standard problems such as shop floor scheduling or lot-sizing, or their simple combinations such as scheduling with batching. Whereas many real-world production planning problems require the simultaneous solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Stawowy e Duda (2012) Duda e Stawowy (2013) propuseram métodos e/ou modelos para o problema de planejamento da produção em fundições de pequeno porte.…”
Section: Introductionunclassified
“…Stawowy e Duda (2012) Duda e Stawowy (2013) propuseram métodos e/ou modelos para o problema de planejamento da produção em fundições de pequeno porte.…”
Section: Introductionunclassified
“…Constraint (5) ensures that only one alloy is produced in each sub-period. Constraint (6) ensures that the capacity of the core shop is not exceeded in a given sub-period. Constraint (7) checks if there is enough cores to be assembled in the mold in order to produce the desired number of items.…”
Section: Lot-sizing and Scheduling Modelmentioning
confidence: 99%
“…More complete review of the papers dealing with production planning in foundries can be found e.g. in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Decision maker must take into account two main criteria: timeliness of orders and maximizing production capacity bottlenecks. The stated problem is described by lot scheduling models, from which the most explored is Mixed Integer Programming model [7]. As exact commercial solvers are impractical for large problem instances, we proposed to apply some heuristic search methods to solve the MIP model.…”
Section: Introductionmentioning
confidence: 99%